THE INFLUENCE OF THE IMPLEMENTATION OF GOOD CORPORATE GOVERNANCE, ACCOUNTABILITY ACCOUNTING AND BUDGETING PARTICIPATION ON THE COMPANY PERFORMANCE IN PDAM SURAKARTA - Nabila Kurniawati; Maya Widyana Dewi; Rukmini Rukmini (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
Abstract: This study aims to examine the effect of implementing good corporate governance, accountability, and mitigation planning on company performance in PDAM Surakarta City. The sampling method used purposive sampling method. Data collection techniques using questionnaires. The analysis used in this research is descriptive statistical analysis, validity and reliability test which are processed using the Statistical Package for Social Science (SPSS) Version 23. The result of the study show that variables of good corporate governance, accountability accounting and budgeting participation have an effect on company performance. Keyword: good corporate governance, accounting per responsibility, budget sensitivity, company performance.